Grass-roots Justice in Ethiopia - Alula Pankhurst, Getachew Assefa (dir.) (Centre français des études éthiopiennes, 2008)
This book presents a timely review of the relations between the formal and customary justice systems in Ethiopia, and offers recommendations for legal reform. The book provides cases studies from all the Region of Ethiopia based on field research on the working of customary dispute resolution (CDR) institutions, their mandates, compositions, procedures and processes. The cases studies also document considerable unofficial linkages with the state judicial system, and consider the advantages as...